A COMPARATIVE ANALYSIS OF EFFECTIVENESS OF LEARNER- CENTRED AND TEACHER-CENTRED METHOD - ZulfizarQochqorova; Isoqjonova Guljahon Doniyor qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. There has been a lot of debate in the education field about the differences between teacher-centered and student-centered teaching. Each approach has its own advantages and disadvantages. Teacher-centered method refers to the traditional educational approach where the teacher is the main authority. On the other hand, student-centered learning encourages students to take an active role in their own learning and focus on their own needs. This comparison and contrast of the two approaches examines the advantages of each.